2014
DOI: 10.5664/jcsm.3878
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Sleep Quality on the Relationship between PTSD and Physical Activity

Abstract: Study Objectives: Physical inactivity is linked to health outcomes such as obesity, diabetes, and psychiatric disorders. Sleep disturbance has been linked to the same adverse outcomes. We examine the infl uence of sleep on physical activity as a novel approach to understand these relationships. Specifi cally, our objective was to determine whether low sleep quality predicts low physical activity in posttraumatic stress disorder (PTSD), a disorder associated with sleep disturbance, physical inactivity, and poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 50 publications
1
25
2
Order By: Relevance
“…It is also quite likely the type, quality, and quantity of these behaviors operate synergistically (Buman et al 2015). For instance, engaging in physical activity has demonstrable and positive effects on one’s sleep habits (Benloucif et al 2004; Dzierzewski et al 2014), while improved sleep has been shown to increase an individual’s ability to engage in physical activity the following day (Dzierzewski et al 2014; Lambiase et al 2013; Talbot et al 2014). Therefore, while reducing sedentary time is likely to have important implications for a number of psychosocial and health outcomes, it is certainly feasible that the activity with which sedentary behavior is substituted (i.e., sleep, light activity, MVPA) is likely to influence the type and magnitude of these effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is also quite likely the type, quality, and quantity of these behaviors operate synergistically (Buman et al 2015). For instance, engaging in physical activity has demonstrable and positive effects on one’s sleep habits (Benloucif et al 2004; Dzierzewski et al 2014), while improved sleep has been shown to increase an individual’s ability to engage in physical activity the following day (Dzierzewski et al 2014; Lambiase et al 2013; Talbot et al 2014). Therefore, while reducing sedentary time is likely to have important implications for a number of psychosocial and health outcomes, it is certainly feasible that the activity with which sedentary behavior is substituted (i.e., sleep, light activity, MVPA) is likely to influence the type and magnitude of these effects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, poor sleep habits have been associated with a number of correlates of retrospective mind wandering, such as impaired working memory function [ 20 , 21 ] and negative affect [ 22 - 24 ]. Moreover, several studies have demonstrated that these habits contribute to lower levels of physical activity [ 25 - 27 ]. If one’s mind wandering is indeed associated with their participation in physical activity, sleep may be an important moderator of this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, in turn, is part of the pathogenesis of numerous chronic illnesses, such as cardiovascular disease, that could impair health and functioning in patients with PTSD (Brudey et al, ). Similarly, poor sleep quality has been linked to a number of psychological and physical health outcomes (Iliescu et al, ; Spira et al, ; Talbot et al, ; Vandrey, Babson, Herrmann, & Bonn‐Miller, ; Wong et al, ), including higher inflammation (for review, see Irwin, Olmstead, & Carroll, ). Taken together with the well‐established negative relationship between PTSD and sleep (Germain, ; Kobayashi, Boarts, & Delahanty, ; Maher, Rego, & Asnis, ), sleep quality likely represents an important target for both treatment and future research.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed sleep quality using a single modified item derived from the Pittsburgh Sleep Quality Index (PSQI), which asks participants to rate their sleep quality during the last month from 0 ( very good ) to 4 ( very bad ; Buysse, Reynolds, Monk, Berman, & Kupfer, ). The PSQI has demonstrated excellent reliability (Buysse et al, ) and the current version of this question has been used in similar populations previously and predicted outcomes such as aggression (Caska et al, ) and physical activity (Talbot, Neylan, Metzler, & Cohen, ).…”
Section: Methodsmentioning
confidence: 99%